Handcrafts productions, identity construction and power dynamics in mapuche communities in Neuquen (Argentina) - Rotman, Mónica B. (Revista de Antropología Social, 2011)
In this article we deal with certain handcrafts production processes of the mapuche communities in the Province of Neuquen, Argentina, making reference to an instance of commercialization, taking into consideration such activity in its double changing symbolic and economic dimension, and in connection with the processes of ethnic identity construction. We firstly present the contextual conditions in which the existence of these groups is inscribed, as well as general characteristics —such as demographical, legal, economic— that refer to the situation of these communities at present. We then analyze the handcrafts production process, examining the special features and dynamics of such, considering that this field has been instituted in one of the spaces where the conformation and legitimacy of the ethnic identity of mapuche producers is discussed. Furthermore, we explain the intervention of state agencies and non-governmental institutions in these processes, understanding that such are inscribed in a frame of inter-ethnic relationships marked by a historical asymmetry.